YIV-906 enhances nuclear factor of activated T-cells (NFAT) activity of T cells and promotes immune checkpoint blockade antibody action and CAR T-cell activity - Lam, Wing; Hu, Rong; Liu, Shwu-Huey; Cheng, Peikwen; Cheng, Yung-Chi (Frontiers in Pharmacology, 2023)
YIV-906 is a systems biology botanical cancer drug, inspired by a traditional Chinese herbal formulation. Results from eight Phase I/II to II clinical studies demonstrated the potential of YIV-906 to prolong survival and improve the quality of life of cancer patients. As an immunomodulator in the tumor microenvironment, YIV-906 can turn cold tumors hot and potentiate anti-tumor activity for different classes of anticancer agents; and as a cytoprotector in the GI, YIV-906 can reduce non-hematological side effects and speed up damaged tissue recovery. YIV-906 enhanced anti-PD1 action against hepatoma in mice by stimulating both innate and adaptive immunity. In a Jurkat cell-staphylococcal superantigen E (SEE)-Raji cell culture model, YIV-906 promoted T cell activation with upregulation of CD69 by enhancing NFAT activity, with or without PD1-PD-L1 interaction. YIV-906 could trigger the phosphorylation of TCR downstream signaling cascades without the involvement of TCR. YIV-906 could inhibit SHP1 and SHP2 activities, which dephosphorylates TCR downstream proteins due to the PD1-PD-L1 interaction. Therefore, YIV-906 could enhance anti-PD1 action to rescue the depressed NFAT activity of Jurkat cells due to the PD1-PD-L1 interaction. In addition, YIV-906 enhanced the NFAT activity and killing capability of Jurkat cells expressing chimeric antigen receptor (CAR-CD19-CD3z) toward CD19 expressing cells, such as Raji cells, with or without PD1-PD-L1 overexpression. Ingredient herb S (Scutellaria baicalensis Georgi) of YIV-906 and some S compounds were found to play key roles in these activities. In conclusion, YIV-906 modulates adaptive immunity by activating T effector cells mainly through its action on SHP1/2. YIV-906 could also facilitate immune checkpoint blockade therapy or CAR-T cell therapy for cancer treatment